IMPROVING TEACHER PERFORMANCE THROUGH STRENGTHENING SCHOOL CULTURE, TRANSFORMATIONAL LEADERSHIP, MANAGERIAL ROLES, AND WORK MOTIVATION - Siswandi, R. Dede; Notosudjono, Didik; Novita, Lina (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
Abstract : This study aims to develop strategies and methods for improving teacher performance through strengthening School Culture, Transformational Leadership, Managerial Roles, and Work Motivation, as well as identifying the influence of these variables on teacher commitment. This study was conducted in “A” accredited private elementary schools in South Tangerang for 12 months, involving 7 sub-districts. The study population included teachers of “A” accredited madrasah aliyah in Bekasi City, spread across 8 sub-districts. Using survey method and quantitative approach, as well as SITOREM analysis technique, this study analyzed primary data collected through questionnaires to measure the variables studied. The results of this study indicate that there is a highly significant positive relationship between School Culture, Transformational Leadership, Managerial Roles, and Work Motivation on Teacher Performance. Hypothesis testing with a correlational statistical model proved that each of these variables significantly influenced the improvement of teacher performance. The results of SITOREM analysis identified key indicators that need to be improved for each variable to improve teacher performance, such as Organizational values, Intellectual Stimulation, Communication in decision making, and Work rewards.